Developing an ontology for cloud–based archive systems. (1st January 2015) - Askhoj, Jan; Sugimoto, Shigeo; Nagamori, Mitsuharu
This paper presents a domain ontology for cloud archives, based in part on the PREMIS Editorial Committee ontology for the PREMIS Data Dictionary. Our ontology's design is based on a layered model of cloud computing where lower layers provide shared services to higher layers. It focuses on the submission of generic Submission Information Packages with PREMIS preservation metadata. An ontology is designed to define a common vocabulary for cloud archives, and define the roles and responsibilities for data creation and transfer, including the registration of cloud–based content creation systems. We define the classes, object properties, data properties and annotations necessary to describe the agents, objects, events and rights that comprise a cloud archive. We evaluated the ontology with a prototype system, using real–world examples of cloud systems, digital objects and metadata. We found that the ontology was able to describe the chosen components successfully, and that it improved metadata interoperability between content creating applications and the services providing preservation metadata.